Effectiveness Of Training Programs In Encouraging Work Productivity: A Study Of Bima District Firefighters - Arkan Sopian; Firmansyah Kusumayadi (Universitas Negeri Gorontalo, 2021)
The purpose of this study was to determine the effect of training on the work productivity of Bima District Fire Department employees. This research is causal associative research using a quantitative approach. The population in this study were 45 Bima Regency Fire Department employees. The sampling technique uses saturated or total population samples. Thus the number of respondents used in this study were 45 people. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis techniques used are simple linear regression, correlation coefficient, coefficient of determination (R2) and t test using the Statistical Product and Service Solution (SPSS) version 21.0. The results showed that the training had a positive and significant effect on the work productivity of Bima District Fire Department employees. these results are evidenced by the significance value smaller than 0.05 (0.001˂0.05).